2010
DOI: 10.1002/icd.663
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in preschool children: temperament or personality?

Abstract: Individual differences among adults have generally been conceptualized in terms of personality theory and traits. In contrast, individual differences among very young children (birth to kindergarten) have generally been conceptualized in terms of temperament theory and traits. The present study compares and contrasts measures of temperament and personality in a sample of preschool children. Temperament traits were assessed with a well-established measure (the Rothbart CBQ), and a new preschool rating instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 28 publications
3
44
0
4
Order By: Relevance
“…The "adventurous" temperament traits identified in this review have been associated with high extraversion and agreeableness and low neuroticism and conscientiousness using the Big Five personality approach (De Pauw & Mervielde, 2010). Specifically, (a) high activity level was associated with high extraversion (Hagekull & Bohlin, 2003), (b) low effortful control and high impulsivity were associated with low conscientiousness (Digman & Shmelyov, 1996;Grist & McCord, 2010;Shafer, 2001) and (c) low negative affectivity was associated with low neuroticism (Grist & McCord, 2010;Hagekull & Bohlin, 2003;Shafer, 2001;Watson & Clark, 1992), low conscientiousness (Farrell, Brook, Dane, Marini, & Volk, 2015;Grist & McCord, 2010) and high agreeableness (Farrell et al, 2015;Shafer, 2001). Besides one study which was prospective (Hagekull & Bohlin, 2003), other studies were concurrent.…”
Section: Interactions Between Temperament and The Family Environmentmentioning
confidence: 84%
“…The "adventurous" temperament traits identified in this review have been associated with high extraversion and agreeableness and low neuroticism and conscientiousness using the Big Five personality approach (De Pauw & Mervielde, 2010). Specifically, (a) high activity level was associated with high extraversion (Hagekull & Bohlin, 2003), (b) low effortful control and high impulsivity were associated with low conscientiousness (Digman & Shmelyov, 1996;Grist & McCord, 2010;Shafer, 2001) and (c) low negative affectivity was associated with low neuroticism (Grist & McCord, 2010;Hagekull & Bohlin, 2003;Shafer, 2001;Watson & Clark, 1992), low conscientiousness (Farrell, Brook, Dane, Marini, & Volk, 2015;Grist & McCord, 2010) and high agreeableness (Farrell et al, 2015;Shafer, 2001). Besides one study which was prospective (Hagekull & Bohlin, 2003), other studies were concurrent.…”
Section: Interactions Between Temperament and The Family Environmentmentioning
confidence: 84%
“…Low and high intensity expressions were differentially associated with child traits. Specifically, high intensity negative expressions predicted higher neuroticism and lower agreeableness and conscientiousness (traits correlated with EC in children and adults; Cumberland-Li, Grist & McCord, 2010;Jensen-Campbell et al, 2002), whereas low intensity negative expressions showed the opposite associations with these traits. These findings suggest that children who engage in a greater number of low intensity expressions and fewer high intensity expressions have more adaptive personality traits of planfulness and compliance, as one would expect for those higher in EC.…”
Section: Associations Between Ec and Pementioning
confidence: 93%
“…Four of the five scales-Extraversion, Agreeableness, Conscientiousness, and Neuroticism-have shown excellent internal reliability in several studies (e.g., Grist & McCord, 2009;Hurt & Grist, 2010;Litty, 2007;McCord, 2006). These same scales correlate very well with similar constructs as measured by established temperament scales (e.g., Grist & McCord, 2010;Scheck & Grist, 2008). However, the Openness scale has thus far performed poorly in terms of both internal reliability and convergent validity.…”
mentioning
confidence: 69%
“…This is a major increase in reliability for Openness to Experience. Coefficient alphas as well as mean interitem correlations are presented in Table 5. PHASE 2-VALIDATION STUDY Grist and McCord (2010) compared preschool teacher ratings of children in their classrooms on the M5-PS-90 and the three temperament scales of the Child Behavior Questionnaire. We reanalyzed their data using the 35-item set.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation